The Effect of nitrogen Fertilization and Potassium Humate on Growth and Nitrogen Utilization Efficiencies of Soft Wheat (Sham 10) under the Costal Conditions - الحافي علاء; غياث علوش; صالح قبيلي (Latakia University Journal -Biological Sciences Series, 2022)
A filed experiment was conducted using a complete randomized block design at Jableh-Bustan saleh in 2018-2019. The aim was to investigate the effect of increasing rates of nitrogen fertilizer (N: 0, 100, 200, 300 and 400 kg N/h-1) and humate (H: 0, 2.5, 5, and 10 kg H/h-1), and their interactions growth and nitrogen utilization efficiencies by soft wheat (cv. Sham 10). The role of humate in efficiency of N application was also investigated. Nitrogen utilization efficiency (NUE) and recovery efficiency (RE) were decreased from (122.2% and 282.3%) at N application rate (100 kg N/h-1) to (84.9% and 119.5%) with 400 kg N/h-1, respectively. The decrease in partial factor productivity (PFP) was to a lesser extend from (60.6) at 100 kg N/h-1 to (44.4) with N application rate of 200 Kg/h-1. Thereafter, PFP values decreased slowly to reach a (25.9) with treatment 400 kg N/h-1. Application of potassium humate significantly affected NUE, RE, and PFP, in which treatments receiving both N and HA application had greater values that those receiving N application alone. Application of 2.5 kg H/h-1 to 100-400 kg N/h-1 led to increased RE values from (282.3, 229, 180, and 119.5 %) to (403.1, 304.5, 242.1, and 140.2 %). PFP values were also increased from (60.6, 44.4, 35.5, and 25.9) to (81.3, 51.8, 45.4, 29.2), respectively. Increasing N application rate led to significantly increased protein content of grain and percent N translocation to gain (NHI). Both variables were also increased even greater when N application rate (100-400 kg/h-1) was combined with the application of humate. Application of 5 kg H/h-1 increased grain protein (%) by about (16.9, 34.4, 12.13, and 1.87 %), respectively.